Optical and electrical characteristics of ZnS/Au/ZnO multilayer with variable Au thicknesses as transparent conductive films via pulsed laser depositon. (September 2022) - Wang, Caifeng; Hu, Bo; Chen, Ligang; Ye, Yingchun
Highlights: A method for preparing high quality ZnS/Au/ZnO transparent conductive films is proposed. The photoelectric performances of ZnS/Au/ZnO films rely on Au thickness are studied. ZnS/Au/ZnO films have the highest average transmittance and the best FOM when Au thickness is 8 nm. Abstract: Transparent and conducting ZnS/Au/ZnO multilayer films were fabricated on quartz glass via pulsed laser depositon at room temperature. The thickness of Au interlayer changed from 2 to 10 nm. The photoelectric properties which are dependent on the Au thickness were studied in detail. For ZnS/Au/ZnO films, three diffraction peaks in the XRD pattern are identified as the (1 1 1) plane of β-ZnS film, the (0 0 2) plane of ZnO film and the (1 1 1) plane of Au interlayer, which indicate the good crystal quality and preferential orientation growth of the films. The FOM of ZnS/Au/ZnO films with 8 nm Au interlayer is higher than that of other ZnS/Au/ZnO films fabricated in this study, and the highest average transmittance in the visible light region is 85.9%. From these results, it is concluded that the photoelectric performance of ZnS/Au/ZnO films with 8 nm Au interlayer is the best, and the films can be used as transparent electrodes.